Polymeric nanocomposites for dehydration of isopropyl alcohol–water mixtures by pervaporation - Kittur, Arjumandbanu Abdulwahab; Madhu, Gattumane Motappa; Rashmi, Sudhina Hulagurmath; Rajanna, Sowmya Surapanhalli; Yaranal, Naveenkumar Ashok (Lviv Politechnic Publishing House, 2018)
Досліджено полімерні нанокомпозитні мембрани полівініловий спирт/ZnO. З використанням методів ІЧ-Фур‘є- і УФ-спектроскопії, рентгено-дифракційного аналізу та скануючої електронної мікроскопії проведено аналіз нанокомпозитних мембран. Встановлено, що мембрани є переважно водосорбційними і водопроникними. Показано що одержані плівки можуть бути ефективно використані для руйнування азеотропної суміші ізопропіловий спирт–вода.

The present work focuses on poly(vinyl alcohol)/ZnO polymer nanocomposite membranes. The nanocomposite membranes are characterized using FTIR, UV-Vis spectra, XRD and SEM techniques. The membranes exhibited preferential water sorption and permeation. Results manifest that the fabricated films can be efficiently utilized to break the azeotropic point of isopropyl alcohol–water mixture.
Полімерні нанокомпозити для дегідрації сумішей ізопропіловий спирт–вода дифузійним випаровуванням
Keywords: дифузійне випаровування; полімерна нанокомпозитна мембрана; суміш ізопропіловий спирт–вода; pervaporation; polymer nanocomposite membrane; isopropyl alcohol–water mixture